2021
DOI: 10.1002/jrsm.1532
|View full text |Cite
|
Sign up to set email alerts
|

The application of AMSTAR2 in 32 overviews of systematic reviews of interventions for mental and behavioural disorders: A cross‐sectional study

Abstract: A measurement tool to assess systematic reviews, version 2' (AMSTAR2) is a 16item tool to critically appraise systematic reviews (SRs) of healthcare interventions.This study aimed to assess the methods and outcomes of AMSTAR2 appraisals in overviews of SRs of interventions for mental and behavioural disorders. The crosssectional study was conducted using 32 overviews of SRs selected from three electronic databases in January 2021. Data items included overview and SR characteristics and AMSTAR2 appraisal method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 33 publications
6
29
0
Order By: Relevance
“…Although this scoping review focused on evaluation strategies rather than outcomes of such evaluations, we performed an appraisal of the 30 systematic reviews included in our study with the AMSTAR2 tool. We found that the overall methodological quality of systematic reviews of digital interventions for physical activity promotion needs improvement, which has already been suggested in the context of other health interventions [ 77 - 79 ]. The overall confidence in the results of systematic reviews of digital interventions for physical activity promotion could be improved by better adherence to established reporting guidelines for systematic reviews and the prospective registration of review protocols.…”
Section: Discussionmentioning
confidence: 81%
“…Although this scoping review focused on evaluation strategies rather than outcomes of such evaluations, we performed an appraisal of the 30 systematic reviews included in our study with the AMSTAR2 tool. We found that the overall methodological quality of systematic reviews of digital interventions for physical activity promotion needs improvement, which has already been suggested in the context of other health interventions [ 77 - 79 ]. The overall confidence in the results of systematic reviews of digital interventions for physical activity promotion could be improved by better adherence to established reporting guidelines for systematic reviews and the prospective registration of review protocols.…”
Section: Discussionmentioning
confidence: 81%
“…This step was necessary to prevent any research waste. According to meta-research [19][20][21], many reviews of interventions in the health context are redundant because they either address the same aims as those addressed by other existing reviews or cite the same primary studies. This problem is so extensive that some reviews do not include any unique primary studies that are not cited in other reviews, and there are as many reviews as or even more reviews than there are primary studies in some fields [19][20][21].…”
Section: Protocol and Registrationmentioning
confidence: 99%
“…According to meta-research [19][20][21], many reviews of interventions in the health context are redundant because they either address the same aims as those addressed by other existing reviews or cite the same primary studies. This problem is so extensive that some reviews do not include any unique primary studies that are not cited in other reviews, and there are as many reviews as or even more reviews than there are primary studies in some fields [19][20][21]. The procedure of checking if a new review is required prior to study registration may be especially necessary in rapidly developing fields, such as digitally supported interventions, or when addressing commonly investigated outcomes, such as PA promotion.…”
Section: Protocol and Registrationmentioning
confidence: 99%
See 2 more Smart Citations